Unusual clinical presentation of lymphoma intestinal: ileosigmoid fistulization. - González, Daniel; Rodríguez, Gustavo; Plazzotta, Cecilia; Rondán, Mariela; Ruso, Luis; Balboa, Oscar (Cirugía del Uruguay, 2003)
Primary intestine lymphomas are a rare occunence, represent approximately 12% of primitive tumors of small intestine and between 0,2% and 0,65% of those found in the colon. Epidemiology has radically changed with respect to the past century, a fact which is specifically linked with the advent of inmuno-suppresion. The analysis involves a clinical case of a non Hodgkin primary lymphoma of intestine with an unusual presentation which, according to REAL classification, modified by PDQ, is an aggressive lymphoma of the T peripheral variety.